Metadata for university artistic collection - Ramos, Aline Cristina Gomes (2023)
This paper aims to explain part of the research conducted in the master's degree in History, Politics and Cultural Assets of the Research and Documentation Center of Contemporary History of Brazil of the Getúlio Vargas Foundation, being to the principle of a metadata scheme for documentation of Brazilian university art collections and collections, based on the case of the Arts Center of the Federal University of Espírito Santo. To this end, it is established the comparison of norms and guidelines, comparing the fields and adopting those with a higher index of repetition and semantic alignment to the specificity of the works. As a result, a systematization is presented with the crosswalk performed from national and international documentation standards, organizing a proposal for surveying and registering the university art collection. It is concluded that the recurrence of metadata demonstrates the degree of importance and indispensable form, being possible to create a consistent and contemporary model for the registration of information in art. In this sense, starting from the issues presented by the object of study and meeting local needs can be an alternative to ensure the applicability and maintenance of the model, leading to the beginning of a thought about data governance.